Inherited Cardiomyopathies Revealed by Clinically Suspected Myocarditis: Highlights From Genetic Testing. (August 2020) - Ader, Flavie; Surget, Elodie; Charron, Philippe; Redheuil, Alban; Zouaghi, Amir; Maltret, Alice; Marijon, Eloi; Denjoy, Isabelle; Hermida, Alexis; Fressart, Véronique; Gandjbakhch, Estelle
Abstract : Supplemental Digital Content is available in the text.